Chemical CD oscillation and chemical resonance phenomena in a competitive self-catalytic reaction system: a single temperature oscillation induces CD oscillations twice. Issue 6 (6th December 2018) - Sawato, Tsukasa; Shinozaki, Yasuhiro; Saito, Nozomi; Yamaguchi, Masahiko
Abstract : Chemical CD oscillation and chemical resonance phenomena appear in a competitive chemical reaction system involving amplification. Abstract : Chemical CD oscillation and chemical resonance phenomena appear in a competitive chemical reaction system involving amplification. A pseudoenantiomeric mixture of an aminomethylenehelicene ( P )-tetramer and an ( M )-hexamer in toluene forms three states, namely hetero-double-helixB, hetero-double-helixC, and dissociated random-coil 2A . When the temperature of the solution is oscillated between −5 and 38 °C at a rate of 2 K min −1, Δ ε reaches maxima twice during a single temperature oscillation, which is called a chemical CD oscillation phenomenon. The phenomenon arises from the sharp competition between the two self-catalytic 2A +C -to-2C and 2A +B -to-2B reactions. In addition, the chemical CD oscillation appears, when temperature oscillation occurs at a rate of 2 K min −1, and higher and lower rates provide a single maximum, a process referred to as the chemical resonance phenomenon. The changes in concentration induced by temperature oscillation repeatedly crossed equilibrium.